Pozyskiwanie danych w badaniach przedsiębiorstw międzynarodowych - doświadczenia praktyczne - Chełpa, Stanisław; Fiącek, Adam; Listwan, Tadeusz (Data acquisition in researching international companies - practical experiences, 2006)
The paper focuses on the issues related to acquiring objects and data in researching business enterprises with the special emphasis placed on international companies. The theoretical model is outlined, in accordance with which the requirements against items belonging to the research sample are formulated. The activities assumed for the completion of the sample and the results of factor analyses performed to X-ray the features of the companies undergoing diagnosis against theoretical presumptions are also described. The paper presents some further research issues and possible directions in exploring the acquired data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 449-457